2020
DOI: 10.1097/pcc.0000000000002541
|View full text |Cite
|
Sign up to set email alerts
|

Association of Acute Kidney Injury With Subsequent Sepsis in Critically Ill Children

Abstract: Objectives: Acute kidney injury is a major cause of morbidity and mortality in critically ill children. A growing body of evidence has shown that acute kidney injury affects immune function, yet little is known about the association between acute kidney injury and subsequent infection in pediatric patients. Our objective was to examine the association of non-septic acute kidney injury with the development of subsequent sepsis in critically ill children. Design: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…Moreover, the present ndings indicate that children with sepsis or infection are three times more likely to develop AKI than their counterparts. This nding is in agreement with studies in China [29], Addis Ababa, Ethiopia [20], Pennsylvania, the USA, and Taiwan [32,33]. This is because sepsis causes profound alteration of circulation and is characterized by the impaired distribution of blood ow, decreasing peripheral vascular resistance, and derangement of microcirculatory perfusions, such as renal vasculature [34,35].…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the present ndings indicate that children with sepsis or infection are three times more likely to develop AKI than their counterparts. This nding is in agreement with studies in China [29], Addis Ababa, Ethiopia [20], Pennsylvania, the USA, and Taiwan [32,33]. This is because sepsis causes profound alteration of circulation and is characterized by the impaired distribution of blood ow, decreasing peripheral vascular resistance, and derangement of microcirculatory perfusions, such as renal vasculature [34,35].…”
Section: Discussionsupporting
confidence: 90%
“…5 After discharge, AKI survivors are at increased risk of developing chronic kidney disease (CKD), end-stage kidney disease, cardiovascular disease and death. 6 Other studies suggest that AKI predisposes to disparate sources of morbidity including infection, [7][8][9][10] bone fracture, 11 stroke, 12 gastrointestinal haemorrhage 13 and dementia. 14 While muscle wasting is well described in patients with CKD, 15 16 the contribution of AKI-RRT to muscle wasting in critically ill patients has not been previously studied.…”
Section: Open Accessmentioning
confidence: 99%
“…36 The primary objective of this study is to characterise longitudinal measures of muscle size (rectus femoris (RF) muscle cross-sectional area (CSA) and muscle thickness (mT)) and quality (echo intensity (EI)) in critically ill adults with AKI requiring CRRT during their ICU stay and in postdischarge follow-up among survivors. This trial protocol was designed using the elements of the Strengthening the Reporting of Observational studies in Epidemiology checklist for cohort studies 9 whenever applicable.…”
Section: Open Accessmentioning
confidence: 99%
“…In this study, after adjusting for confounding variables, the was a 3.6-fold greater odds of subsequent infection in neonates with postoperative AKI ( 98 ). In a single center retrospective cohort study, a higher odds of infection in a single center study of 5,000 critically ill children: there was a non-linear increase in risk for sepsis based on AKI severity, with stage 3 AKI patients incurring the greatest risk for sepsis ( 99 ). A small single center study of pediatric patients receiving CRRT also found an association with infection, that occurred a median of 11 days after CRRT initiation ( 101 ).…”
Section: Aki and The Effects On Other Organ Systemsmentioning
confidence: 99%